Self-Efficacy and Entrepreneurial Behavior of Horticultural Young Farmers in the Special Region of Yogyakarta Indonesia - Nurlaela, Siti; Hariadi, Sunarru Samsi; Raya, Alia Bihrajihant (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to analyze the level of self-efficacy and entrepreneurial behavior and the effect of self-efficacy on entrepreneurial behavior. Data collection is done through a closed questionnaire with a quantitative approach. The research location was in the horticultural center in the Special Region of Yogyakarta, Indonesia. This research used simple random sampling method, which gathers data from 300 young horticultural farmer respondents. Data analysis was performed using linear regression analysis. The results of the study stated that self-efficacy has a positive effect on entrepreneurial behavior. The magnitude of the effect of self-efficacy on entrepreneurial behavior (p≤0.01) or R Square of 15.1%. The government is expected to further facilitate young farmers with the development of young farmers groups, training, apprenticeships, and business assistance so that they can increase their self-efficacy. Theoretical and practical implications of the findings are also discussed along with recommendations for improvement farmer regeneration program by the Ministry of Agriculture. environmental, planning, organizational, transportation, and traffic regulation.